1997
DOI: 10.1046/j.1365-2958.1997.5471908.x
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies sequence differences in the Mip protein from the genus Legionella: implications for function and evolutionary relatedness

Abstract: SummaryThe nucleotide sequence of the mip genes and their inferred amino acid sequences were determined from 35 Legionella species and compared with the published sequences for L. pneumophila, L. micdadei and L. longbeachae. The sequences were 69-97% conserved at the nucleotide level and 82-99% at the amino acid level, with total conservation of amino acids determined to be associated with sites known to be involved in peptidyl prolyl cis-trans isomerase activity. No apparent difference could be determined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
2
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 39 publications
0
46
2
6
Order By: Relevance
“…The mip gene encodes Mip, which has been reported to play a significant role in virulence (2). It has been shown that mip is useful for the discrimination of Legionella species (19,20). However, incongruences have been found between the phylogenies elucidated from the 16S rRNA gene and mip sequences (8,20).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The mip gene encodes Mip, which has been reported to play a significant role in virulence (2). It has been shown that mip is useful for the discrimination of Legionella species (19,20). However, incongruences have been found between the phylogenies elucidated from the 16S rRNA gene and mip sequences (8,20).…”
mentioning
confidence: 97%
“…Legionellosis is usually acquired in the community and accounts for 2 to 15% of all community-acquired pneumonia that requires hospitalization in the United States (27). So far, of the more than 40 Legionella species that have been characterized and classified by various methods (8,30), 21 have been reported to be pathogenic to humans (20,30) A classification scheme constructed by various methods can be efficiently used for the rapid and precise identification of clinical isolates in the diagnostic laboratory. One of these methods is the determination of molecular phylogenetic relationships or typing (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also serological evidence associating LLAPs with respiratory disease in humans (Rowbotham, 1993 ;Benson et al, 1995). The grouping together of members of the genus Legionella is based on phenotypic similarities and is supported by molecular techniques (Brenner et al, 1985 ; Brenner, 1986 ;Fry et al, 1991 ;Harrison & Saunders, 1994 ;Hookey, 1995 ;Benson et al, 1996 ;Hookey et al, 1996 ;Ratcliff et al, 1997Ratcliff et al, , 1998. There are few discriminatory phenotypic tests for the differentiation of Legionella species (Benson & Fields, 1998 ;Harrison & Saunders, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…(1, 7), 5S ribosomal DNA (7), 16S ribosomal DNA (11,12,14,16), and the 23S-5S spacer (15). While the mip gene was initially used as an L. pneumophila-specific marker (2), other legionellae were also found to harbor this gene (3,13). The 5S and 16S rRNA genes are such well-conserved regions that it is difficult to differentially detect L. pneumophila and other Legionella species on a real-time basis without subsequent tests (7,14) or that there is a risk of amplification of the DNAs of other than Legionella species (4).…”
mentioning
confidence: 99%